Efficacy of Foliar Applications of Entomopathogenic Nematodes in the Management of the Invasive Tomato Leaf Miner Phthorimaea absoluta Compared to Local Practices Under Open-Field Conditions - Joelle N. Kajuga; Bancy W. Waweru; Didace Bazagwira; Primitive M. Ishimwe; Stephano Ndacyayisaba; Grace C. Mukundiyabo; Marie Mutumwinka; Jeanne d’Arc Uwimana; Stefan Toepfer (Agronomy, 2025)
The tomato leaf miner Phthorimaea (syn. Tuta) absoluta (Lepidoptera: Gelechiidae) is invasive in many agricultural regions. Its larvae feed inside leaf mines and tomato fruits, causing yield losses. Repeated sprays of insecticides disrupt agri-ecosystems. Conducting three open-field tomato experiments, we assessed whether formulations of entomopathogenic nematodes could improve the efficacy of these promising biocontrol agents or whether other nature-based agents such as pyrethrin or spinosad would be the better option(s), as compared to a standard insecticide. Steinernema carpocapsae formulated in an alkyl polyglycoside polymeric surfactant, in canola oil, or mixed in both reduced 37 to 68% of pest larvae within two weeks post-treatment, followed by the botanical pyrethrin (48%). Neither spinosad nor lambda cyhalothrin achieved sufficient control. Increasing the frequency of treatments to every two weeks moderately increased efficacy. Positively, the nematodes can, if properly formulated and applied, still be recovered alive from leaf surfaces up to two hours after spraying, indicating that they have time to enter the leaf mines. A small proportion can even be still extracted alive from the leaf mines one week later. Despite these promising results, further research is needed to improve the efficacy of nature-based management options for use against this pest, with the aim of ultimately reducing reliance on chemical insecticides and minimizing the impact on agri-ecosystems.